Tourism for Economic Prosperity in Gandaki Province of Nepal - Khatiwada, Shreekanta S.; Sharma, Ramji; Ranabhat, Suresh (Kalika Journal of Multidisciplinary Studies, 2024)
Tourism is a multidimensional mega industry interconnected with hospitality services and facilities. It generates assorted business connectivity with transportation, accommodation, food and beverage, entertainment, nature, culture and adventure business and facilities. Obviously, tourism has some significant implications over the local economy at community as well as destination level. However, the variance of tourism impacts on various districts and provinces of Nepal mainly depends on the availability and abundance of tourism products, activities and the level of hospitality practices of the destinations. This study, therefore, is an attempt to analyze the potentiality of tourism as an opportunity for economic prosperity in Gandaki Province of Nepal based on the economic contributions of major tourism components of the province. The trend of visitors’ flow, people’s involvement in tourism as entrepreneurs, volume of revenue generation and the number of employment creation are major variants of analysis for this paper. The paper is based on qual-quan method of analysis with partial use of secondary date published from tourism related authorities and organizations whereas a focus group discussion of the leaders of tourism entrepreneurs’ associations and the representations of concerned authorities is the major source of primary information. The study has come up with the finding that there is a huge potentiality of tourism development and an ample opportunity for economic prosperity via tourism in Gandaki province and hence suggested to incorporate tourism in the plans and policies of the province as a crux of development mainly through the involvement of local community, enhancement of village tourism and promotion of adventure tourism activities and products in the province.